Physical quality, amino acid contents, and health risk assessment of straw mushroom (Volvariella volvacea) at different maturity stages - Mohd Joha, Nur Sakinah; Misran, Azizah; Tengku Muda Mohamed, Mahmud; Abdullah, Sumaiyah; Mohamad, Azhar (Faculty of Food Science and Technology,Universiti Putra Malaysia, 2021)
Volvariella volvacea, also known as straw mushroom, is an edible mushroom, and a highly nutritious food source. In Malaysia, tremendous increase in the consumption of this mushroom is due to its characteristics; short cropping duration, distinct flavour, and pleasant taste. During harvesting, the maturity of V. volvacea is vital to obtain high quality produce. As the mature stage quickly succeeds the immature stage, farmers usually collect both the immature and mature stages at harvest. Thus, the objective of the present work was to evaluate the physical quality, nutrients, and health risk assessment of V. volvacea at both maturity stages. The mushrooms were cultivated on composted empty fruit bunch (EFB), and harvested after a week at immature (button) and mature (veil opening) stages. The absence of spores at the button stage could lower the metabolic activity after harvest, thus decelerating the deterioration rate. Button stage mushrooms showed significantly higher firmness and higher content of glutamic acid. In term of safety, both stages were within the dietary intake limit for heavy metals. In conclusion, the button stage could be suitable and practical for consumption and commercialisation.